The impact of diorama media on learning outcomes in water cycle education - Sadewo Witjaksono; Kasriman Kasriman (Universitas Pendidikan Indonesia, 2025)
Learning Natural and Social Sciences (IPAS) on the water cycle in elementary schools still poses challenges for helping students understand abstract concepts such as evaporation, condensation, and precipitation. Diorama media were chosen because they provide a concrete, interactive, three-dimensional visual representation. This study used a quasi-experimental design with a pretest-posttest control group design involving an experimental group using diorama media and a control group using conventional methods. Data were analyzed using descriptive and inferential statistics, including paired t-tests and effect size calculations. The results showed that the experimental group's average post-test score was significantly higher than that of the control group, with a medium effect size. Diorama media not only improve students' understanding of the water cycle concept but also encourage active involvement and motivation. The effectiveness of dioramas can be explained through the theories of constructivism, multimedia learning, dual coding, and cognitive load. This study recommends integrating diorama media into the IPAS curriculum in elementary schools, particularly for abstract and complex materials. Abstrak Pembelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) pada materi siklus air di sekolah dasar masih menghadapi tantangan dalam membantu murid memahami konsep abstrak seperti evaporasi, kondensasi, dan presipitasi. Media diorama dipilih karena mampu menghadirkan representasi visual tiga dimensi yang konkret dan interaktif. Penelitian ini menggunakan desain eksperimen semu dengan pretest-posttest control group design yang melibatkan kelompok eksperimen menggunakan media diorama dan kelompok kontrol menggunakan metode konvensional. Data dianalisis menggunakan statistik deskriptif dan inferensial, termasuk uji t berpasangan dan perhitungan effect size. Hasil penelitian menunjukkan bahwa rata-rata skor post-test kelompok eksperimen lebih tinggi secara signifikan dibandingkan kelompok kontrol dengan nilai effect size kategori sedang. Media diorama tidak hanya meningkatkan pemahaman konsep siklus air secara kognitif, tetapi juga mendorong keterlibatan aktif dan motivasi murid. Efektivitas diorama dapat dijelaskan melalui teori konstruktivisme, multimedia learning, dual coding, dan cognitive load. Penelitian ini merekomendasikan integrasi media diorama dalam kurikulum IPAS di sekolah dasar, khususnya pada materi yang bersifat abstrak dan kompleks. Kata Kunci: hasil belajar; media diorama; siklus air